EVALUATION OF HAPPINESS AMONG SPECIALITY MEDICAL DOCTORS WORKING IN PRIVATE HOSPITALS IN INDIA: A QUALITATIVE RESEARCH - Mahobia, Ashish; Mahobia, Swati; Tiwari, Rahul VC; Managutti, Anil; Tiwari, Heena (International Journal of Psychosocial Rehabilitation, 2020)
Aim of the study: This study aimed to investigate factors that affect happiness among various speciality medical doctors in the departments of ENT, Gynaecology, Ophthalmology, General Medicine and General Surgery working in private hospitals in India. Methodology: Our study consisted of 800 speciality doctors working in 45 private hospitals in India. An closed-ended questionnaire was sent to the survey participants by Email. Responses of 654 doctors were received which included 108 ENT surgeons, 112 Gynaecologists, 103 Ophthalmologist, 172 General Physicians and 159 General Surgeons which were then subjected to descriptive statistical analysis. The questions were based upon various factors which affected the quality of life as well as job satisfaction and happiness in general in the survey participants. Results: Our study showed that the ENT specialists were far more work-loaded than desired with around 55 % of them were not satisfied with the salary. In the case of Gynaecologists, Job satisfaction overall coped better with around 70% of them gave positive responses. Whereas in case of Ophthalmologists, they were not satisfied with the increased workload that they endured; around 51 % gave negative responses. Data on General surgeons showed that they had physical health issues with around 57 % of negative responses. Most of the General Physicians were not satisfied with their salaries (58%). Conclusion: Present study depicted that our speciality doctors need more of salary satisfaction as well as better mental health strategies to cope with the increased amount of stress in the medical professional life.